Clean(ish) : eat (mostly) clean, live (mainly) clean, and unlock your body's natural ability to self-clean - Stephens, Gin (St. Martin's Griffin, 2022)
"In Gin Stephens's New York Times bestseller Fast. Feast. Repeat., she taught you how to fast (completely) clean as part of an intermittent fasting lifestyle. Now, whether you're an intermittent faster or not, Gin shows you how to become clean(ish) where it counts: you'll learn how to eat (mostly) clean and live (mainly) clean to unlock your body's natural ability to self-clean. Instead of aiming for perfection (which is impossible) or changing everything at once (which is hard, and never leads to lasting results), you'll cut through the confusion, lose the fear, and embrace the freedom that comes from becoming clean(ish). As you learn how to lower your toxic load through small changes, smart swaps, and simple solutions, you'll evolve simply and easily toward a clean(ish) lifestyle that works for you"--